The Impact of Professional Competence and Leadership Style on Employee Performance at the Indonesian Maritime Adiguna Polytechnic Medan - Ginting, Suratni (Universitas Syiah Kuala, 2025)
The Indonesian Maritime Adiguna Polytechnic Medan, as a maritime education institution, is governed by Law Number 13 of 2003 on Manpower, which outlines regulations regarding employee rights, obligations, working conditions, rules, and the validity period of company policies. To achieve its vision and mission, the institution relies on employees who are professional, knowledgeable, and experienced, supported by an effective leadership style. This study investigates the impact of professional competence and leadership style on employee performance, both individually and collectively. Using SPSS for data analysis, the findings reveal that professional competence has a significant positive effect on employee performance, contributing 34.2% with a t-value of 2.734 and a p-value of 0.007. Leadership style also shows a substantial positive effect, accounting for 61.7% with a t-value of 6.275 and a p-value of 0.000. When analyzed together, professional competence and leadership style collectively influence employee performance by 83.7%, leaving 16.3% attributed to other factors outside the scope of this study. Among the two variables, leadership style demonstrates a stronger influence on employee performance. In conclusion, the study highlights that employee performance at the Indonesian Maritime Adiguna Polytechnic Medan is significantly driven by both professional competence and leadership style. Enhancing these two aspects is critical for the institution to successfully develop superior human resources in the maritime sector.